2001
DOI: 10.1007/s007260170025
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of surfactants with living cells.

Abstract: The toxicity of new surfactants containing a beta-lactam ring has been established by studying their interaction with a hybridoma cell line. An hour of contact is sufficient to generate an apoptotic signal after two days of culture. Under the experimental conditions chosen for the experiments, surfactants have been divided into three categories: i) biocompatible and non-apogenic; ii) surfactants triggering an apoptotic signal without inducing cell necrosis; iii) surfactants triggering an apoptotic signal at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It has been proposed that high concentrations of surfactants cause necrosis whereas low concentrations induce apoptosis [53]. Enomoto and co-workers [54] demonstrated that some cationic surfactants, such as benzalkonium chloride, induce apoptosis at very low concentration (below CMC) by causing structural changes on the plasma membrane, such as phosphatidylserine translocation, but anionic and amphoteric surfactants could not induce apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that high concentrations of surfactants cause necrosis whereas low concentrations induce apoptosis [53]. Enomoto and co-workers [54] demonstrated that some cationic surfactants, such as benzalkonium chloride, induce apoptosis at very low concentration (below CMC) by causing structural changes on the plasma membrane, such as phosphatidylserine translocation, but anionic and amphoteric surfactants could not induce apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic surfactant molecules can induce cell apoptosis or necrosis depending on the concentration of the surfactant [52,53]. The surfactant molecules at a high concentration (near or above CMC) may form mixed micelles with membrane lipids, which may solubilize cell membranes.…”
Section: Mechanisms Of Surfactant Effects On Biodegradation Of Pahsmentioning
confidence: 99%
“…Since the latter do not possess any metabolic activity that could induce apoptosis, when a compound shows haemolytic activity it can be considered as a chaotropic agent, able to alter and cause disorder in the membrane of erythrocytes. Compounds with a chaotropic impact on erythrocyte membranes could exert a similar effect also on the membranes of other cell types [11].…”
Section: Haemolysis Assaymentioning
confidence: 99%
“…*Address correspondence to this author at the Dipartimento di Scienze Farmaceutiche, Città Universitaria, viale A. Doria, 6; I-95125 Catania, Italy; E-mail: r.pignatello@unict.it Similarly, N-acyl lipoamino acids have been widely studied also for their effects on erythrocytes and cell membranes, and potential toxicity [10][11][12]. Like lipopolysaccharides, some natural conjugates of lipids and amino acids present in bacterial sources can act as endotoxins for the human body [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation